Eco-label, kepedulian lingkungan, dan perilaku pembelian hijau: Sebuah sudut pandang Generasi Z tentang semen ramah lingkungan - Putri Rahmi Mardius; Sulastri Sulastri; Muchsin Saggaf Shihab; Yuliani Yuliani (Jurnal Manajemen Maranatha, 2023)
The research aims to examine the effect of eco-label on green purchase behavior (GPB) mediated by environmental concerns (EC). Moreover, this testing of the related impact is based on the perception of four hundred and eleven people from Generation Z becoming the samples, taken by purposive sampling technique. Furthermore, their responses are captured by survey distributing questionnaires and analyzed by the structural equation model based on a partial least square. Once testing the hypotheses, this study demonstrates a positive influence of eco-label on GPB and EC. This positive sign also exists in the association between EC and GPB. Hence, the mediation effect of EC is proven. Based on this evidence, marketers setting Generation Z as their target should promote their goods: cement, based on eco-label, and place their products at easily identified locations.